ANALISIS PENGARUH PERENCANAAN DAN PENYERAPAN ANGGARAN TERHADAP KEMISKINAN: (Studi Pada Kabupaten/Kota di Provinsi Maluku) - Jancen Roland Patty (P3M Politeknik Negeri Ambon, 2025)
The purpose of the study was to analyze the influence of budget planning and absorption on poverty in regencies/cities in Maluku Province. The type of research is a causal relationship or relationship between variables and this study is a census study, namely a study that uses all members of the population as samples. The data used are secondary data in the form of periodic data (cross section), namely poverty data, planning, and budget absorption in 11 regencies/cities in Maluku Province. Data testing through multiple linear regression analysis with a significance level of 0.005. The results of the study prove that the budget planning variable has a significant influence on the poverty variable. This is evidenced by the results of the t-statistic test which shows a probability value or significant value of 0.025 below the significance level of 0.05. Furthermore, the budget absorption variable has a significant influence on the Poverty variable. This is evidenced by the results of the t-statistic test which shows a probability value or significant value of 0.034 below the significance level of 0.05 Keywords: Budget Planning. Budget Absorption, Poverty